2021
DOI: 10.1111/his.14378
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2‐negative IGH‐BCL2 translocation‐negative follicular lymphoma of the thyroid differs genetically and epigenetically from Bcl‐2‐positive IGH‐BCL2 translocation‐positive follicular lymphoma

Abstract: Bcl-2-negative IGH-BCL2 translocation-negative follicular lymphoma of the thyroid differs genetically and epigenetically from Bcl-2-positive IGH-BCL2 translocation-positive follicular lymphoma Aims: Follicular lymphoma (FL), comprising a minor subset of primary thyroid lymphomas, is divided into two groups based on Bcl-2 expression and IGH-BCL2 translocation. The clinicopathological features exhibited by Bcl-2-negative IGH-BCL2 translocation-negative FL of the thyroid (Bcl-2 -/IGH-BCL2 -tFL) are different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 41 A recent study with relatively few cases demonstrated the lack of chromatin modifying gene mutations but no special mutations were identified. 71 Similar cases have been reported in the ovary 39 and other extranodal sites; however, no genetic information is available. Nevertheless, all these extranodal lymphomas present with localized disease (stage IE), predominantly large cell cytology, often diffuse growth areas, diminished CD10 expression, and excellent prognosis compared with their t(14:18)-positive counterpart.…”
Section: Alternative Forms Of T(14;18)-negative Flmentioning
confidence: 60%
See 2 more Smart Citations
“… 41 A recent study with relatively few cases demonstrated the lack of chromatin modifying gene mutations but no special mutations were identified. 71 Similar cases have been reported in the ovary 39 and other extranodal sites; however, no genetic information is available. Nevertheless, all these extranodal lymphomas present with localized disease (stage IE), predominantly large cell cytology, often diffuse growth areas, diminished CD10 expression, and excellent prognosis compared with their t(14:18)-positive counterpart.…”
Section: Alternative Forms Of T(14;18)-negative Flmentioning
confidence: 60%
“… 35 Two of these features support systemic disease. Interestingly, the mutational profile of PCFCL is similar to other extranodal t(14;18)-negative FLs, 41 , 69 , 70 , 71 suggesting that inactivation of TNFRSF14 might play a role in the development of t(14;18)-negative lymphomas. The exact mechanism of TNFRSF14 mutations promoting FL lymphomagenesis remains to be elucidated.…”
Section: Alternative Forms Of T(14;18)-negative Flmentioning
confidence: 81%
See 1 more Smart Citation
“…All tissue specimens were fixed in 10% formalin and neutral buffered solution, embedded in paraffin, cut into 4 μm thick serial sections, and used for both hematoxylin and eosin staining and immunohistochemical (IHC) staining. The latter was performed using the Roche BenchMark ULTRA IHC/ISH Staining Module (Ventana Medical Systems) according to the manufacturer’s instructions and a previous study 12. The primary antibodies used in this study, dilution ratios, and positive controls are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The latter was performed using the Roche BenchMark ULTRA IHC/ISH Staining Module (Ventana Medical Systems) according to the manufacturer's instructions and a previous study. 12 The primary antibodies used in this study, dilution ratios, and positive controls are listed in Table 2. The antibodies for MUC1 (H23), MUC5AC (MRQ- 19), and MUC6 (MRQ-20) used in our analysis were connected to the tandem-repeat domain.…”
Section: Hematoxylin and Eosin Staining And Immunohistochemistrymentioning
confidence: 99%